Pharmacokinetics of pazufloxacin in buffalo calves after single subcutaneous administration - SHARMA, S K; ADITI, ADITI (The Indian Journal of Animal Sciences, 2015)
The pharmacokinetics and urinary excretion of pazufloxacin was investigated in buffalo calves following a single subcutaneous administration (5 mg/kg b.wt.). Pharmacokinetic analysis of disposition data indicated that subcutaneous administration data were best described by 1-compartment open model. The peak plasma levels of pazufloxacin were 1.12±0.05 μg/ml at 45 min and the drug was detected up to 16 h. The absorption half-life and elimination half-life were 0.26±0.04 h and 3.01±0.18h, respectively. The apparent volume of distribution and total body clearance were 2.96±0.20 L/kg and 0.67±0.02 L/kg/h, respectively. The urinary excretion of pazufloxacin in 24 h was 23.8±2.30 % of total administrated dose. From the data of surrogate markers (AUC/MIC, Cmax/MIC), it was determined in the buffalo calves that when administered by the subcutaneous route at 5 mg/kg, pazufloxacin is likely to be effective against bacterial isolates with MIC < 0.05 μg/ml.